Financial reporting and analysis - Foley, Bob. (Canterbury : Institute of Financial Services, 2004)
Includes how to relate accounting information to actual business decisions, how to recognize economically useful information in statements and reports. uses international accounting standards and shows how to analyze weaknesses as well as strengths of published financial statements.
Includes index.
oif 19/03/15
Loan
Keywords: Financial statements; Corporations -- Accounting